Changing international health policy and changing international development goals - Pupavac, Vanessa (Sage, 2008)
The World Health Organisation (WHO) was founded in 1948 with a remit to promote public health around the world. The WHO’s constitution sets out its objective as ‘the attainment by all peoples of the highest possible level of health’ (WHO, 1948). The paper raises broad questions over the aspirations and practice of international health policy in its international political and development context. The paper explores how international health policy has been informed by evolving international development strategies, from the earlier modernisation approaches to the sustainable development approaches of recent decades. The final part considers international health policy today in a world of continuing international inequalities.